K63-Linked Ubiquitination Targets Toxoplasma gondii for Endo-lysosomal Destruction in IFNγ-Stimulated Human Cells. - Barbara Clough; Joseph D Wright; Pedro M Pereira; Elizabeth M Hirst; Ashleigh C Johnston; Ricardo Henriques; Eva-Maria Frickel (PLoS Pathogens)
Toxoplasma gondii is the most common protozoan parasitic infection in man. Gamma interferon (IFNγ) activates haematopoietic and non-haematopoietic cells to kill the parasite and mediate host resistance. IFNγ-driven host resistance pathways and parasitic virulence factors are well described in mice, but a detailed understanding of pathways that kill Toxoplasma in human cells is lacking. Here we show, that contrary to the widely held belief that the Toxoplasma vacuole is non-fusogenic, in an immune-stimulated environment, the vacuole of type II Toxoplasma in human cells is able to fuse with the host endo-lysosomal machinery leading to parasite death by acidification. Similar to murine cells, we find that type II, but not type I Toxoplasma vacuoles are targeted by K63-linked ubiquitin in an IFNγ-dependent manner in non-haematopoetic primary-like human endothelial cells. Host defence proteins p62 and NDP52 are subsequently recruited to the type II vacuole in distinct, overlapping microdomains with a loss of IFNγ-dependent restriction in p62 knocked down cells. Autophagy proteins Atg16L1, GABARAP and LC3B are recruited to <10% of parasite vacuoles and show no parasite strain preference, which is consistent with inhibition and enhancement of autophagy showing no effect on parasite replication. We demonstrate that this differs from HeLa human epithelial cells, where type II Toxoplasma are restricted by non-canonical autophagy leading to growth stunting that is independent of lysosomal acidification. In contrast to mouse cells, human vacuoles do not break. In HUVEC, the ubiquitinated vacuoles are targeted for destruction in acidified LAMP1-positive endo-lysosomal compartments. Consequently, parasite death can be prevented by inhibiting host ubiquitination and endosomal acidification. Thus, K63-linked ubiquitin recognition leading to vacuolar endo-lysosomal fusion and acidification is an important, novel virulence-driven Toxoplasma human host defence pathway.